Reduced Sensory-Evoked Locus Coeruleus-Norepinephrine Neural Activity in Female Rats With a History of Dietary-Induced Binge Eating - Bello, Nicholas T.; Yeh, Chung-Yang; James, Morgan H. (Frontiers in Psychology, 2019)
Noradrenergic pathways have been implicated in eating pathologies. These experiments sought to examine how dietary-induced binge eating influences the neuronal activity of the locus coeruleus (LC)-norepinephrine system. Young adult female Sprague Dawley rats (7-8 weeks old) were exposed to a repeated intermittent (twice weekly) cycle of 30-min access to a highly palatable sweetened fat (i.e., vegetable shortening with 10% sucrose) with or without intermittent (24 h) calorie restriction (Restrict Binge or Binge groups, respectively). Age- and weight-matched female control rats were exposed to standard chow feeding (Naive group) or intermittent chow feeding (Restrict group). The Binge and Restrict Binge groups demonstrated an escalation in sweet-fat food intake after 2.5 weeks. On week 3, in vivo single unit LC electrophysiological activity was recorded under isoflurane anesthesia. Restrict Binge (20 cells from 6 rats), and Binge (27 cells from 6 rats) had significantly reduced (approximate 20% and 26%, respectively) evoked LC discharge rates compared with naive rats (22 cells, 7 rats). Spontaneous and tonic discharge rates were not different among the groups. Signal-to-noise ratio was reduced in the groups with intermittent sweetened fat exposure. In order to investigate the neuropeptide alterations as a consequence of dietary binge eating, relative gene expression of neuropeptide Y (NPY), glucagon-like peptide 1 receptor (GLP-1r), prodynorphin, and related genes were measured in LC and hypothalamic arcuate (Arc) regions. Glp-1r, Npy2r, and Pdyn in LC region were reduced with repeated intermittent restriction. Npy1r was reduced by approximately 27% in ARC of Restrict compared with Naive group. Such data indicate that dietary-induced binge eating alters the neural response of LC neurons to sensory stimuli and dampen the neural stress response.